Government funds and demographic transition: alleviating ageing costs in a small open economy - Helvi Kinnunen (Bank of Finland, 2008)
This paper investigates public pension funding using a dynamic general equilibrium macroeconomic model (DSGE) that facilitates investigation of distortionary effects of fiscal and pension policy responses to ageing. The model is calibrated to the Finnish economy, which will encounter substantial ageing pressures in the near future. During the transition to an older population structure ageing costs can be substantially lowered by allowing public funds to smooth out the tax responses. Cutting down on pension prefunding at a time when the pace of ageing is at its peak reduces the necessary tax hikes and stimulates labour supply growth at the moment when the labour market is tightest. With smaller funding needs, ageing leads to a slower growth in labour costs, a better employment conditions and faster production growth.
URN:NBN:fi:bof-20140807334
Keywords: E13; H55; J11; J26; 330; ageing; general equilibrium; public finance; government funds